Acetone-induced graphene oxide film formation at the water-air interface - Wei, Li (2013)
Graphene oxide (GO) is an amphiphilic soft material, which can accumulate at the water–air interface. However, GO sheets diffuse slowly in the aqueous phase because of their large size. It is still challenging to form high quality GO films in a controllable and simple way. In this study, we showed that GO sheets can quickly migrate to the water–air interface and form thin films when a suitable amount of acetone is directly mixed with a GO aqueous dispersion. The film formation rate and surface coverage of GO sheets depend on the volume of acetone added, GO dispersion concentration, and formation time. Among several organic solvents, acetone has its advantage for GO film formation owing to its three properties: a nonsolvent to GO aqueous dispersions, miscible with a GO aqueous dispersion, and fast evaporation. Furthermore, we have found that the film formation also is governed by the size of GO sheets and their oxygen content. Although smaller GO sheets could migrate to the water–air interface faster, the overlapping of small GO sheets and the increase in contact resistance is not desirable. A higher oxygen content in GO sheets could also result in smaller GO sheets. Multilayer GO films can be obtained through layer-by-layer dip-coating. These findings open opportunities in developing simple scalable GO film fabrication processes.